Factors related to dropout intention of medical college postgraduates in China: A comparison between students who receive standardized training and non-standardized training. - Haiyang Li; Jing Tong; Xue Jiang; Dan Gu; Xiaoning Zhang; Bin Hu (PLoS ONE)
Introduction The global shortage of healthcare workers significantly impacts patient well-being and physician workforce development. Ensuring the graduation of every medical student is a critical way to maintain an adequate physician workforce. However, previous studies have shown that dropout intention is very high among medical college postgraduates in China. Therefore, there is a high need to investigate the factors associated with dropout intention among Chinese medical college postgraduates to prevent dropout intention and dropout rates. Methods A cross-sectional study was conducted in December 2023 in Jiangsu Province, China. A total of 1042 postgraduates participated in the survey, with an effective response rate of 97.4%. The survey included postgraduates' demographic characteristics, tutor-postgraduate interaction, research training environment, general psychological distress, and fear of future violence at work. The forward multivariate stepwise logistic regression was used to explore the factors related to dropout intention in medical college postgraduates who receive standardized training and non-standardized training, respectively. Results We found that 16.5% of medical college postgraduates had an intention to drop out, with 13.0% among those in standardized training and 19.6% among those in non-standardized training. For the standardized training group, age, tutor-postgraduate interaction (professional ability interaction), and fear of future violence at work were risk factors for dropout intention, while a positive research training environment and high research self-efficacy were identified as protective factors. For the non-standardized training group, the father's education and stress were risk factors, while satisfaction with the research degree program, tutor-postgraduate interaction (comprehensive cultivation interaction), and high research self-efficacy were protective factors. Conclusion Factors influencing the dropout intention of medical college postgraduates in China vary between those who receive standardized training and non-standardized training. Chinese medical colleges and relevant education departments should develop personalized strategies for these two groups of students to reduce the dropout intention and dropout rate.